The ethical conduct of nutrition undergraduates at a public university in Brazil - Sousa, Raphaela Cruz Vasconcelos; Carvalho, Natália Caldeira de; Mendonça, Raquel de Deus (O Mundo da Saúde, 2024)
The practice of academic misconduct seems to be routine in undergraduate studies. Therefore, addressing ethical conduct in training is a starting point to promote debate on the construction of knowledge. This study aimed to analyze the academic misconduct of nutrition undergraduates. A cross-sectional study was performed with Nutrition students at a public university in Brazil. Participants included 105 students took part in the study: 42.9% were on the 1st to the 5th semesters and 57.1% on the 6th to the 9th semesters. Students on the final semesters had a higher prevalence of “letting the colleagues copy the answers” (p=0.05), “using ready-made work” (p=0.04), and “included their name on a paper without collaboration” (p=0.01). The main motivations for academic misconduct were: colleagues cheating (71.4%), believing that professors had committed misconduct (70.5%), difficult subjects (52.4%), and maintaining good grades (50.5%). Students on the last semesters reported lack of time (p=0.05) as a reason, and 10.5% mentioned having performed nutrition appointments without supervision. Given the high prevalence of academic misconduct in undergraduate courses, it is suggested that the discipline on ethics be taught in the initial semesters, in addition to offering courses and conversation circles on intellectual property, ethical conduct, time management, and teaching methodologies.